FAKTOR-FAKTOR YANG MEMPENGARUHI KUNJUNGAN BAYI DAN BALITA KE POSYANDU DI KELURAHAN CAMBAYA KECAMATAN UJUNG TANAH KOTA MAKASSAR - Sitti Mukarramah; Hidayati Hidayati; Indar Sukriani (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2022)
Posyandu is a form of community-based health effort that is managed and organized from, by, for and with the community. Posyandu is held to empower the community and provide convenience for the community to obtain basic basic or social health services to accelerate the reduction in maternal mortality and infant mortality. The purpose of this study was to determine the factors that influence the visit of infants and toddlers to the posyandu in the Cambaya Village, Ujung Tanah District, Makassar City, South Sulawesi Province in 2019. The research method is analytic survey with cross sectional design. Sampling using the